Analysis of Factors Affecting Rice Farmers' Intentions in the Use of Smart Farming Technology in Kanigoro Village, Pagelaran Sub-District, Malang Regency - Aulia, Syifa; Riana, Fitria Dina; Hartono, Rachman; Nugroho, Tri Wahyu; Meitasari, Deny; Rahman, Moh. Shadiqur (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2025)
The low adoption of smart farming technology among farmers, despite the availability of tools in Kanigoro Village, Pagelaran Subdistrict, is the main issue addressed in this study. Technologies such as the Smart Soil Sensor and Bird Control Sound System have not been optimally utilized, even though they can improve agricultural efficiency and productivity. This study aims to analyze the influence of attitude, subjective norm, and perceived behavioral control on farmers’ intention to adopt smart farming technology, using the Theory of Planned Behavior (TPB) framework. The research employed a quantitative approach involving 100 rice farmers, with data collected through structured questionnaires and direct interviews. Data were analyzed using Structural Equation Modeling - Partial Least Square (SEM-PLS) with the help of WarpPLS 7.0 software. The results show that all three independent variables-attitude, subjective norm, and perceived behavioral control-have a positive and significant effect on farmers’ intention. Among these, perceived behavioral control has the most dominant influence, followed by subjective norm and attitude. These findings suggest that beyond building positive attitudes, it is essential to strengthen social support and increase farmers' confidence in their ability and access to technology to enhance the adoption of smart farming practices.